Continued improvement of cardiovascular mortality in Hungary - impact of increased cardio-metabolic prescriptions - Jozan Peter; Papp Renata; Balogh Sandor; Csaszar Albert (BMC, 2010)
Abstract Background During the last 35 years the poor ranking of Hungary on the list of life expectancy at birth among European countries, has not changed. In 1970 our lag behind the leading European countries was the smallest. The gap was growing between 1970 and 1993 but from 1994 onwards the life expectancy at birth in Hungary has increased continuously and somewhat faster than in other European countries. The aim of this study was to analyze the association between decreasing cardiovascular mortality rates, as a main cause of death and the increase in cardio-metabolic prescriptions and possible changes in lifestyle behavior. Methods Analyses were conducted on national data concerning cardiovascular mortality and the number of cardio-metabolic drug prescription per capita. The association between yearly rates of cardiovascular events and changes in antihypertensive, antilipidemic and antidiabetic prescription rates was analyzed. The changes in other cardiovascular risk factors, like lifestyle were also considered. Results We observed a remarkable decline of mortality due to stroke and acute myocardial infarction (AMI). The fall was significantly associated with all prescription rates. The proportion of each treatment type responsible for suppression of specific mortality rates is different. All treatment types comparably improved stroke mortality, while antilipidemic therapy improved AMI outcome. Conclusions These results emphasize the importance of a comprehensive strategy that maximizes the population coverage of effective treatments. Hungary appears to be at the beginning of the fourth stage of epidemiologic transition, i.e. it has entered the stage of delayed chronic noninfectious diseases.